Local Autonomy, Tax Morale and the Shadow Economy - Benno Torgler; Friedrich Schneider; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Policymakers often propose strict enforcement strategies to fight the shadow economy and to increase tax morale. However, there is also a bottom-up approach such as, for example, decentralizing the political power to those who are close to the problems. Thus, this paper analyses the relationship between local autonomy and tax morale or the size of the shadow economy. We use data on tax morale at the individual level and macro data of the size of the shadow economy to systematically analyse the relevance of local autonomy and compliance in Switzerland, a country where the degree of federalism varies across different cantons. The findings suggest that there is a positive (negative) relationship between local autonomy and tax morale (size of the shadow economy).
Keywords: H26; H73; D70; 330; Tax Morale; Shadow Economy; Tax Compliance; Tax Evasion; Local Autonomy; Federalism; Institution